2007
DOI: 10.1002/pola.22442
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of phthalazinone units in sulfonated poly(arylene ether ether ketone ketone) copolymers as proton exchange membrane materials

Abstract: A new series of aromatic poly(arylene ether ether ketone ketone) copolymers containing pendant sulfonic acid groups (SPAEEKK-D) were synthesized from commercially available monomers 1,3-bis(4-fluorobenzoyl)-benzene, sodium 6,7-dihydroxy-2-naphthalenesulfonate, and 4-(4-hydroxyphenyl)-2,3-phthalazin-1-one (DHPZ). Structure-property relationships of the phthalazinone SPAEEKK-D series poly(arylene ether ether ketone ketone) copolymer were compared with copolymers SPAEEKK-B and SPAEEKK-H containing different diols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…All the membranes were not broken into pieces before 3 h treatment. The SPPEK-DMs membranes exhibited better oxidative stability than previously reported sulfonated poly(phthalazinone ether ketone) and other sulfonated poly(aryl ether ketone)s [20,25,42,43] . It has been known that the oxidative attack by HO· and HOO· radicals occurs mainly on the main chain of aromatic rings bound with electron-donating ether groups.…”
Section: The Oxidative Stability Of Sppek-dmsmentioning
confidence: 85%
“…All the membranes were not broken into pieces before 3 h treatment. The SPPEK-DMs membranes exhibited better oxidative stability than previously reported sulfonated poly(phthalazinone ether ketone) and other sulfonated poly(aryl ether ketone)s [20,25,42,43] . It has been known that the oxidative attack by HO· and HOO· radicals occurs mainly on the main chain of aromatic rings bound with electron-donating ether groups.…”
Section: The Oxidative Stability Of Sppek-dmsmentioning
confidence: 85%
“…This behavior can be attributed to the presence of water content in the membranes. The hydrated WO 3 can transfer protons to the form of H x WO 3 23, 24. The conductivity of SPPESK/WO 3 (30 wt%) composite membrane was measured at 100 °C under different RH values.…”
Section: Resultsmentioning
confidence: 99%
“…For the same reason, Kim and Guiver synthesized sulfonated poly(etheretherketoneketone) SPEEKK molecules with sulfonated naphthyl rings as side chains: the obtained membrane exhibited improved mechanical and thermal properties and oxidation stability. [57] In another example, Chen et al designed and synthesized a novel sidechain-sulfonated aromatic polyimide, and the highlight was a desulfonation temperature as high as 350 8C. [58] In addition, Xing and Kerres compared the effect of the location of SO 3 H in the main chain on the stability of sulfonated poly(arylene ether)s, and the results suggested that sulfonic acid groups at the meta position to the ether or sulfone groups have higher thermal and chemical stability and higher proton conductivity than those at the ortho position to ether and sulfone.…”
Section: Optimization Of the Position Of So 3 Hmentioning
confidence: 97%